Differences in phenotypes, symptoms, and survival in patients with cardiomyopathy—a prospective observational study from the Sahlgrenska CardioMyoPathy Centre - Ljungman, C.; Bollano, E.; Rawshani, A.; Nordberg Backelin, C.; Dahlberg, P.; Valeljung, I.; Björkenstam, M.; Hjalmarsson, C.; Fu, M.; Mellberg, T.; Bartfay, S.-E.; Polte, C. L.; et al. (Frontiers in Cardiovascular Medicine, 2023)
Introduction Cardiomyopathies is the fourth most common cause of heart failure. The spectrum of cardiomyopathies may have been affected by changes in environmental factors and the prognosis by modern treatment. The aim of the study was to create a prospective clinical cohort; the Sahlgrenska CardioMyoPathy Centre (SCMPC) study and compare patients with cardiomyopathies regarding phenotype, symptoms and survival. Methods The SCMPC study was founded in 2018 including patients with all types of suspected cardiomyopathies. The SCMPC study included data on patients’ characteristics, background, family history, symptoms, diagnostic examinations, and treatment including heart transplantation and mechanical circulatory support (MCS). Patients were categorized in type of cardiomyopathy based on the diagnostic criteria from the European Society of Cardiology (ESC) working group on myocardial and pericardial diseases. Primary outcome was death, heart transplantation or MCS, analyzed by Kaplan-Meier and Cox proportional regression, adjusted for age, gender and left ventricular ejection fraction (LVEF) at baseline. Results In all, 461 patients, 73.1% men with a mean age of 53.6 ±16 years were included. The most common diagnosis was dilated cardiomyopathy (DCM) followed by cardiac sarcoidosis and myocarditis. Dyspnea was the most common initial symptom in patients with DCM and amyloidosis, while patients with arrhythmogenic right ventricular cardiomyopathy (ARVC) presented with ventricular arrythmias. Patients with ARVC, Left-ventricular non-compaction cardiomyopathy (LVNC), Hypertrophic cardiomyopathy (HCM) and DCM had the longest time from debut of symptoms until inclusion in the study. Overall, 86% of the patients were alive without heart transplantation or MCS after 2.5 years. The primary outcome differed between the cardiomyopathies, where ARVC, LVNC and cardiac amyloidosis had the worst prognosis. In a Cox regression analysis ARVC and LVNC was independently associated with an increased risk of death, heart transplantation or MCS compared with DCM. Further female gender, lower LVEF and wider QRS width was associated with an increased risk of the primary outcome. Conclusions The SCMPC database offers a unique opportunity to explore the spectrum of cardiomyopathies over time. There is a large difference in characteristics and symptoms at debut and remarkable difference in outcome where ARVC, LVNC and cardiac amyloidosis posed the worst prognosis.